Using an iPad® App to Improve Sight Word Reading Fluency for At-Risk First Graders. (May 2015) - Musti-Rao, Shobana; Lo, Ya-yu; Plati, Erin
We used a multiple baseline across word lists design nested within a multiple baseline across participants design to examine the effects of instruction delivered using an iPad® app on sight word fluency and oral reading fluency of six first graders identified as at risk for reading failure. In Study 1, three students participated in teacher-directed iPad® instruction to learn sight words. In Study 2, three other students participated in self-mediated iPad® instruction. We measured sight word fluency and oral reading fluency in both studies; In addition, we measured academic engagement in Study 2. Results showed increases in sight word fluency during the iPad® instruction, but limited gains were seen in oral reading fluency. The three participants in Study 2 consistently achieved high levels of engagement during the iPad® instruction compared with engagement during independent reading time. The benefits of using technology in the classroom and directions for future research are discussed.